2003
DOI: 10.1089/10763270360728035
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Plasma-Polymerized Surface Suitable for the Transplantation of Keratinocyte–Melanocyte Cocultures for Patients with Vitiligo

Abstract: The purpose of this study was to develop a convenient methodology for the coculture of autologous melanocytes and keratinocytes for grafting of patients with vitiligo. While grafting of pure melanocytes may achieve repigmentation, the inclusion of keratinocytes ensures rapid reepithelialization. Previously we have used confluent sheets of keratinocytes (with melanocytes present) to transfer cells. However, we found that as the keratinocyte density increased, melanocyte number and function were downregulated. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…More recent work [24] investigating alternative strategies for co-culturing keratinocytes and melanocytes, looked at using a plasma polymerisation technique to coat hydrophobic surfaces such as glass coverslips and also tissue culture plastic. This work showed that keratinocytes could successfully be grown on nitrogen-containing plasma polymer surfaces without the use of a fibroblast feeder layer (which is usually required for keratinocyte survival on tissue culture plastic using standard media for keratinocyte culture).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent work [24] investigating alternative strategies for co-culturing keratinocytes and melanocytes, looked at using a plasma polymerisation technique to coat hydrophobic surfaces such as glass coverslips and also tissue culture plastic. This work showed that keratinocytes could successfully be grown on nitrogen-containing plasma polymer surfaces without the use of a fibroblast feeder layer (which is usually required for keratinocyte survival on tissue culture plastic using standard media for keratinocyte culture).…”
Section: Discussionmentioning
confidence: 99%
“…Cultures were set up in both Green's and M2 media and were re-fed with fresh media after a period of 24 h. Experiments were sacrificed after a period of 4 days and stained with S100. Four days was chosen as a suitable end point from previous work in the group, which showed that melanocyte numbers increased until day 3 in culture and then stabilised between days 3 and 7 [24]. Once fixed and stained, cultures were photographed and then melanocyte numbers were evaluated microscopically by counting all melanocytes present in a 1 cm 2 graticule grid placed over the centre of each well.…”
Section: Assessment Of Melanocyte Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, researchers in the field have successfully developed many delivery systems for skin cells in culture for burn and wound therapy (Bianco and Robey 2001;Boyce and Warden 2002;Harding et al 2002;Naughton and Griffith 2002;Beck et al 2003;Auger et al 2004;Boulton et al 2004;Ehrlich 2004;Eriksson and Vranckx 2004;Jimenez and Jimenez 2004;Lysaght and Hazlehurst 2004). The polymer scaffolds that have been shown to be good as delivery systems for skin cell culture include hyaluronic acid membrane, Hydroderm TM polyurethane-based membrane, Biobrane TM wound dressing, Vicryl TM (polygalactic acid) and Dexon TM suture materials, chitosan, poly (e-caprolactone) films ( (Bianco and Robey 2001;Boyce and Warden 2002;Harding et al 2002;Naughton and Griffith 2002;Beck et al 2003;Auger et al 2004;Boulton et al 2004;Ehrlich 2004;Eriksson and Vranckx 2004;Jimenez and Jimenez 2004;Lysaght and Hazlehurst 2004)). A number of tissue engineered skin products based on or derived from these materials have been approved for use in clinical practice in the USA as well as Europe.…”
Section: Discussionmentioning
confidence: 99%
“…A number of tissue engineered skin products based on or derived from these materials have been approved for use in clinical practice in the USA as well as Europe. Examples of which are LASERSKIN â , TransCyte â , Dermagraft â ( (Bianco and Robey 2001;Boyce and Warden 2002;Harding et al 2002;Naughton and Griffith 2002;Beck et al 2003;Auger et al 2004;Boulton et al 2004;Ehrlich 2004;Eriksson and Vranckx 2004;Jimenez and Jimenez 2004;Lysaght and Hazlehurst 2004).…”
Section: Discussionmentioning
confidence: 99%